2021
DOI: 10.47104/ebnrojs3.v3i4.217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program on Nurses' Knowledge, Practices and Patients' Outcomes Post Total Knee Arthroplasty

Abstract: Context: Total knee arthroplasty (TKA) is a surgical procedure in which the damaged parts of the patient's kneecap, thighbone, and shinbone are replaced with artificial parts. Aim: This study aimed to evaluate the effect of an educational program on nurses' knowledge, practices, and patients' outcomes post total knee arthroplasty. Methods: A quasi-experimental design was utilized in the orthopedic department and outpatient orthopedic clinic affiliated to Benha University Hospital from the beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Concerning total score of nurses' practices regarding pre and postoperative care of patient with total knee arthroplasty, more than two thirds of the studied nurses had incompetent level of practices regarding pre and postoperative care of patient with total knee arthroplasty. This result is identical with a study done by Taha & Ibrahim, (2021), entitled effect of educational program on nurses' knowledge, practices and patients' outcomes post total knee arthroplasty which showed that less than one third of studied nurses had a competent level of practice scores. Moreover, the current results were in consistent with Healy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Concerning total score of nurses' practices regarding pre and postoperative care of patient with total knee arthroplasty, more than two thirds of the studied nurses had incompetent level of practices regarding pre and postoperative care of patient with total knee arthroplasty. This result is identical with a study done by Taha & Ibrahim, (2021), entitled effect of educational program on nurses' knowledge, practices and patients' outcomes post total knee arthroplasty which showed that less than one third of studied nurses had a competent level of practice scores. Moreover, the current results were in consistent with Healy.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding demographic data (age) most of the studied nurses were with a mean age 26.71±4.26 years, this result was in identical line with Aldakheel, (2021), a study performed to assess nurses" knowledge concerning knee arthroplasty and illuminated that more than half of the studied nurses aged between 20-29 years old. On the same line, this result agreed with the study conducted by El-Sayed et al (2016) (2015), who reported that most studied nurses had a Baccalaureate degree in nursing education, also not agreed with Taha & Ibrahim, (2021), which revealed that two third of studied nurses had secondary school nursing education. Concerning years of experience in orthopedic unit, more than two thirds of studied nurses ranged from 1-6 years of experience in orthopedic unit, these results was in line with Aldakheel, (2021), that revealed that most of studied nurses had between 1 to 8 years of experience, Also, those results concur with a study done by Causey-Upton, et al (2020), a study performed to assess orthopedic nurses' perceptions of preoperative education for total knee replacement, revealed that most of nurses working in the orthopedic units ranged from 1-10 years of experience.…”
Section: Discussionsupporting
confidence: 88%